2000
DOI: 10.1093/ajcn/72.1.241s
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in the past and its relevance to developing countries today

Abstract: High maternal mortality was a feature of the Western world from the mid-19th century, when reliable record keeping commenced, to the mid-1930s. During this time, maternal mortality rates tended to remain on a high plateau, although there was wide disparity between countries in the height of the plateau. From Ϸ1937, maternal mortality rates began to decline everywhere, and within 20 y, the intercountry differences had almost disappeared. The decline in maternal mortality rates was so dramatic that current rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 8 publications
0
148
0
5
Order By: Relevance
“…Sharp decline in maternal mortality rates after 1930s in developed country were due to standard of maternal care provided by skilled birth attendants [5,6] Evaluation of safe motherhood initiative program in 1997 also concluded that a skilled attendant to assist childbirth is the single most critical…”
Section: Introductionmentioning
confidence: 99%
“…Sharp decline in maternal mortality rates after 1930s in developed country were due to standard of maternal care provided by skilled birth attendants [5,6] Evaluation of safe motherhood initiative program in 1997 also concluded that a skilled attendant to assist childbirth is the single most critical…”
Section: Introductionmentioning
confidence: 99%
“…In general, developing countries perform better in human development than in income per head terms -although not to the extent suggested by the conventional UNHDI (Crafts, 2002 and has still to be achieved in Africa. This is the result of the public provision of health (McKeown et al, 1975;McKinley and McKinley, 1977;Loudon, 2000;Cutler and Miller, 2005) and education that increased more than proportionally to income per head. Trends in human development result from those exhibited by each of its dimensions.…”
Section: Introducing the 'Improved' Index Of Human Developmentmentioning
confidence: 99%
“…Furthermore, in 2005, real per capita GDP in Latin America, Asia and Africa were similar to that of OECD by the early 1950s, 1920 and mid-19th century, respectively, whereas OECD income per head in 1913 was not reached in Latin America until the late 1960s, up to 2000 in Asia, and has still to be achieved in Africa. This is the result of the public provision of health (McKeown et al, 1975; McKinley and McKinley, 1977;Loudon, 2000;Cutler and Miller, 2005) and education that increased more than proportionally to income per head. Trends in human development result from those exhibited by each of its dimensions.…”
mentioning
confidence: 99%
“…Research shows that those declines were attributable to the quality of care from midwives for home birth deliveries. Where deliveries were by physicians in hospitals, often using chloroform and forceps in otherwise uncomplicated births, maternal mortality was much higher (Loudon 2000). So high maternal mortality was less about knowledge per se but about whose knowledge counted, and that is about power structures within the health system.…”
Section: The Nature Of the Evidencementioning
confidence: 99%